Global solar UV index : a practical guide (Geneva, 2005)
"A marked increase in the incidence of skin cancers has been observed in fair-skinned populations worldwide since the early 1970s. This is strongly associated with personal habits in relation to sun exposure and its ultraviolet (UV) component, and the societal view that a tan is desirable and healthy. The Global Solar UV Index (UVI) described in this document was developed in an international effort by WHO in collaboration with WMO, UNEP and ICNIRP, and is a simple measure of the UV radiation level at the Earth’s surface. It serves as an important vehicle to raise public awareness and to alert people about the need to adopt protective measures when exposed to UV radiation. Intersun, WHO’s Global UV Project, aims to reduce the burden of disease resulting from exposure to UV radiation by assessing and quantifying health risks, and developing an appropriate response through guidelines, recommendations and information dissemination."